Wildlife health capacity enhancement in Thailand through the World Organisation for Animal Health Twinning Program - Suwanpakdee, Sarin; Sangkachai, Nareerat; Wiratsudakul, Anuwat; Wiriyarat, Witthawat; Sakcamduang, Walasinee; Wongluechai, Peerawat; Pabutta, Choenkwan; Sariya, Ladawan; Korkijthamkul, Waruja; Blehert, David S.; White, C. LeAnn; Walsh, Daniel P.; et al. (Frontiers in Veterinary Science, 2024)
There is an increasing need for robust wildlife health programs that provide surveillance and management for diseases in wildlife and wild aquatic populations to manage associated risks. This paper illustrates the value of a systematic method to enhancing wildlife health programs. The U.S. Geological Survey and Mahidol University, Faculty of Veterinary Science, Thailand National Wildlife Health Center formally twinned under the auspices of the World Organisation for Animal Health to enhance wildlife health capacity in Thailand and the Southeast Asia Region. We used a system-wide approach to holistically and interdependently enhance capacity. The project commenced with a wildlife health program needs assessment, and capacity enhancement focused on strengthening the general wildlife health surveillance network and improving wildlife health information management. Activities included partner surveys, interactive and didactic workshops, and individual personnel training. Topics included development of wildlife health information management systems, analysis of the current surveillance network, development of a Theory of Change for a strengthened surveillance network, planning workshops to create a wildlife health network, training on wildlife disease outbreak investigation and field sample collection, leading networks, and individual training on bioinformatics and laboratory techniques. Engagement of stakeholders at all levels, continuous communication throughout the project, use of both strategic planning tools and pedagogical methods, and using iterative and adaptive approaches, were key factors to the success of this project.